Development of Customs Fiscal Function in Latvia - Rudzītis Normunds; Čevers Aldis (Economics and Business)
Globalization of the world economy and increased international trade in economic development of countries seriously affect Customs Services and changes customs functions. Moreover, the measurement efficiency and effectiveness of Customs Services are determined based on an accurate identification of the customs functions to be performed and on the basis of the amount of dynamic analysis. The article shows that significant reduction of the customs fiscal function is identified in the period when Latvia joined the EU Customs Union. The reduction took place due to the country’s efforts to improve business environment and strengthen the competitiveness of enterprises, as well as to improve tax administration system.